2010
DOI: 10.1007/s11102-010-0237-4
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to cabergoline: progression from initially responsive micro to macroprolactinoma

Abstract: In a recent issue of this Journal, Behan et al.[1] published a case of secondary resistance to cabergoline in a patient with prolactinoma. We communicate another case of this exceptional circumstance.A 40-year old woman was submitted to us for study of hyperprolactinemia, spontaneous galacthorrea and secondary amenorrhea, all of which had started one year earlier. She had previous diagnoses of rheumatoid arthritis and idiopathic thrombocytopenic purpurae, which had not required treatment. The initial study sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Only six such patients have been reported in the literature (excluding malignant transformation) (3,4,5,6,7). The possible explanations for acquired non-responsiveness include non-compliance, onset of gonadal steroid replacement that causes dopamine resistance in the lactotrophs, and, rarely, transformation to carcinoma (37,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only six such patients have been reported in the literature (excluding malignant transformation) (3,4,5,6,7). The possible explanations for acquired non-responsiveness include non-compliance, onset of gonadal steroid replacement that causes dopamine resistance in the lactotrophs, and, rarely, transformation to carcinoma (37,41).…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few reported cases of prolactinoma exhibiting secondary resistance, i.e. cases that show an initial response to dopamine agonists, but then become refractory with prolonged treatment (3,4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Only a small subset of patients with prolactinomas does not respond to DAs treatment (primary resistance), as approximately 20-30% is resistant to BRC and around 10-20% to CAB (24,45), due to modification of DRs expression or to intracellular molecular mechanisms. Very infrequently patients with prolactinomas experience a delayed resistance becoming refractory to DAs prolonged treatment (secondary resistance) (46)(47)(48)(49)(50)(51). This condition is generally considered an expression of a negative prognosis as it might indicate a malignant transformation of the prolactinoma (46).…”
Section: Dopamine Agonists Resistance In Pituitary Tumorsmentioning
confidence: 99%
“…As a result, a decrease in D2 receptor expression levels will cause the failure of DAs to inhibit prolactin and further lead to DA resistance in prolactinoma [ 5 ]. Studies have shown that the reduction of dopamine D2 receptor expression is considered to be the main cause of DA resistance in prolactinoma [ 6 8 ], but DRD2-mediated resistance cannot explain all the issues. Therefore, it is urgent to explore the mechanism of drug resistance in prolactinoma.…”
Section: Introductionmentioning
confidence: 99%